Respuesta a la aplicación de tres bioestimulantes en dos variedades de Quinua (chenopodium quinoa willd.) en el cantón Espejo, provincia del Carchi - Guerrero García, Edwin Marcelo (2015)
The presently investigation work was carried out in the canton Espejo, county of the Carchi, located to 3000 mols, in the coordinates geographical 00 º 36 `982" of north latitude and 77 º 56 ` 496 `` of longitude west. The objective of the investigation was to evaluate the answer of three-root stimulant of the system radicular in two quinoa varieties (Chenopodium quinoa Walld). The treatments were 14 formed by the quinoa varieties Tunkahuan and Pata de Venado, with root stimulant application Sintex in dose of 600 and 800 cc/ha, Radisol 800, 1000 and 1200 cc/ha; two witness that were the two varieties without application was also included. The design that was used was that of Complete Blocks at random with factorial arrangement (3 x 2 x 2 + 2). The evaluated data were percentage of germination of the seed, plant height to the 30, 60 and 90 days, diameter of the shaft, number of cobs and yield of the grain. According to the results it was determined that: of the varieties INIAP Tunkahuan and Pata de Venado with root stimulant application Sintex in dose of 600 cc/ha responded positively to the agronomic behavior, however for germination, plant height and shaft diameter the variety Tunkahuan has the best answer; but it stops yield and economic analysis the variety Pata de Venado responded appropriately